Glucocorticoid induced group 2 innate lymphoid cell overactivation exacerbates experimental colitis - Feng, Bingcheng; Lin, Lin; Li, Lixiang; Long, Xin; Liu, Chao; Zhao, Zixiao; Li, Shiyang; Li, Yanqing (Frontiers in Immunology, 2022)
Abnormal activation of the innate and adaptive immune systems has been observed in inflammatory bowel disease (IBD) patients. Anxiety and depression increase the risk of IBD by activating the adaptive immune system. However, whether anxiety affects innate immunity and its impact on IBD severity remain elusive. This study aimed to investigate the mechanism by which anxiety contributes to IBD development in a murine model of acute wrap restraint stress (WRS). Here, we found that anxiety-induced overactivation of group 2 innate lymphoid cells (ILC2) aggravated colonic inflammation. Overactivation of hypothalamic-pituitary-adrenal (HPA) axis is a character of physiological change of anxiety. Corticosterone(CORT), the stress hormone , is a marker of HPA axis activation and mainly secreted by HPA activation. We hypothesized that overproduction of CORT stimulated by anxiety exacerbated colonic inflammation due to abnormally elevated function of ILC2. The results showed that ILC2 secreted more IL-5 and IL-13 in WRS mice than in control mice. Meanwhile, WRS mice experienced more body weight loss, shorter colon length, higher concentrations of IL-6 and TNF-α, more severely impaired barrier function, and more severe inflammatory cell infiltration. As expected, the serum corticosterone levels were elevated after restraint stress. Dexamethasone (DEX) was then injected to mimic HPA axis activation induced CORT secretion. DEX injection can also stimulate ILC2 to secrete more type II cytokines and exacerbate oxazolone(OXA) induced colitis. Blocking the IL-13/STAT6 signaling pathway alleviated colitis in WRS and DEX-injected mice. In conclusion, the overactivation of ILC2 induced by CORT contributed to the development of OXA-induced colitis in mice.